Ứng dụng phương pháp tiệm cận hệ thống trong điều khiển quá trình công nghệ nhiệt điện - Châu, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
The purpose of this paper is to present a result in the problem of control system for thermoelectric and technological process by using a system approach.